A List of social vespid wasps (Hymenoptera:vespidae)from Kuala Lompat, Krau wildlife reserve,Pahang, Peninsular Malaysia. - Nicholas , A.S; Jun-Inchi Kojima; Roslan , M.Y; Fauzi , M; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2011)
A total of 272 social vespid specimens consisting of 210 and 62 specimens which collected during this study and previously collected which have been kept in CIS as voucher specimens respectively were examined and of this 22 social vespids species belonging to the there subfamilies, stenogastrinae (8 species in 3 genera), Polistinae (8 species in 3genera)and vespinae (6 species in 2 genera)were successfully recorded for Kuala Langatwith 12 species are new record for this area.Two previously recorded species namely the L.campanulae and V.multimaculata were not collected in the study. In comparison to those recorded from Peninsular Malaysia,Borneo,Sunda Islands (not including Borneo and Thailand , the collection from Kuala Lompat represents only 31.8% of thr total known species occurred for peninsular Malaysia, 35.5% for Borneo,27.5% for Sunda Island and 44% for Thailand. Interestingly all the species found in Kuala Lompat during this study were also found in the Sunda Islands but only 19 and 14 species collected were also previously recoded in Borneo and Thailand , respectively.